Análise de escrita científica na formação de pesquisadores - Santos, Natan Wellington Kreuz dos (2019)
Searching to understand the writing challenges students face in their researches, this paper presents an investigation conducted with students of a “Scientific Publishing Writing Methodology” discipline of a master’s degree class in 2015-2016. The theoretical support was grounded on the theories of textual genres and the concept of academic literacy in an exploratory qualitative and quantitative research. The research was divided between two complementary stages: in the first exploratory stage the data was collected through two questionnaires with five open and five closed questions each, one at the beginning of the Scientific Writing Methodology class, and one at the end of it; the second stage was bibliographical, where five published abstracts, of the same class of students, were analyzed. The results revealed, among other aspects, that the lack of familiarity with academic textual genres can be the cause of great difficulties in disseminating the knowledge produced by the researchers. However, the awareness about the importance of writing skills can take them to a bigger commitment and engagement when it comes to this task. So, since scientific writing has been underexplored and under investigated on graduation and post-graduation levels, this experience can add information and elements, allowing the debate to be expanded in academic environments, thus bringing to light the relevancy of the matter and creating opportunities for the practice of scientific writing.